Serous ovarian tumors: Immunohistochemical profiling as an aid to grading and understanding tumorigenesis - Manu, V. (Med J Armed Forces India, 2020)
BACKGROUND: The aim of this study was to evaluate the expression of p53, p16, Wilms tumor gene (WT1), and Mindbomb E3 Ubiquitin Protein Ligase 1 (MIB-1) index by immunohistochemical (IHC) staining in benign, low-grade, and high-grade serous ovarian tumors. METHODS: Forty-one cases of ovarian serous tumors were included in the study (benign serous tumor [n = 10], low-grade ovarian serous carcinoma [n = 8], and high-grade ovarian serous carcinoma [n = 23]). Expression of p53, p16, WT1, and MIB-1 by IHC was evaluated statistically with the grade of tumor. Semiquantitative scoring system for percentage (0–5) and intensity (1–3) of staining pattern was used to bring about objectivity. RESULTS: p53, p16, and WT1 showed significantly higher staining scores in ovarian serous carcinoma group than in the benign group (p < 0.05). However, p16 score was not significant in benign versus low-grade tumors. In the carcinoma group, the high-grade serous tumors showed significantly higher staining scores of p53, p16, and WT1 than the low-grade serous tumors (p < 0.05). Papillary serous tumors had comparatively lower p53 and WT1 scores for the same grade of tumor. MIB-1 scores were not significant. CONCLUSION: p53, p16, and WT1 are helpful for the subtyping of serous ovarian tumors as low grade and high grade. WT1 is helpful in establishing primary ovarian serous tumors. The combination of moderate-to-high p53 and WT1 scores provides a robust way of confirming high-grade tumors.